2018
DOI: 10.1111/labr.12135
|View full text |Cite
|
Sign up to set email alerts
|

Agency Theory and Work from Home

Abstract: Wages for individuals working from home have converged toward, and even exceeded, those of office‐workers. I argue that these changes are driven by the ability of firms to monitor employees working from home. Using American Community Survey and Census data spanning 1980–2014, I find wage differentials have shifted from a 26 per cent penalty in 1980 to a 5 per cent premium in 2014. Furthermore, I find that higher wage variance (44 per cent greater in 1980) for home‐workers disappears by 2013. Changes in varianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Between 1980 and 1990, the wage penalties fell fastest in IT-intensive occupations. More recently, using the 1980-2014 ACS and Decennial Census data and controlling for selection using a Heckman selection model, White (2019) found that home-based workers earned a 5 percent wage premium in 2014. Using an instrumental variables technique and U.S. data, Heywood, Seibert, and Wei (2007) found a positive wage differential for WFH but not for other workplace practices.…”
Section: Wage Effects Of Teleworkmentioning
confidence: 99%
“…Between 1980 and 1990, the wage penalties fell fastest in IT-intensive occupations. More recently, using the 1980-2014 ACS and Decennial Census data and controlling for selection using a Heckman selection model, White (2019) found that home-based workers earned a 5 percent wage premium in 2014. Using an instrumental variables technique and U.S. data, Heywood, Seibert, and Wei (2007) found a positive wage differential for WFH but not for other workplace practices.…”
Section: Wage Effects Of Teleworkmentioning
confidence: 99%
“…The pre-pandemic wage premium or discount associated with WFH varies greatly with observable worker characteristics, occupation, and WFH intensity(Pabilonia and Vernon, 2021). Average wages associated with WFH evolved from a large discount in 1980, conditional on controls, to a modest premium by 2014(White, 2019).…”
mentioning
confidence: 99%
“…It has also benefited some companies during the difficult times of the pandemic. Companies have adopted the WFH model, relying on modern technology to reduce the corresponding regulatory costs ( White, 2019 ).…”
Section: Impact Of Wfh On Enterprises Employees and Hr Practitionersmentioning
confidence: 99%